Ring band-pass filter (RBPF) for global positioning system (GPS): article - Abdul Halim, Nazatul Fariza; Ismail, Kamariah (Faculty of Electrical Engineering, 2009)
This paper presents the design, simulation and analysis of a band-pass filter based on ring shape for microwave application. In designing the filter, Tschebycheff approach was used and simulation was carried out using commercial simulation software. The prototype filter was fabricated on the RT Duroid 4350B dielectric substrate (εr) with the value of 3.48. The operating frequency is from 1.559 to 1.610 GHz with the cut-off frequency at 1.584 GHz and bandwidth of 51MHz.